Social Dominance Orientation in Agrarian Resources Accumulation in Coastal Area Indonesia - Saharuddin, Saharuddin; Falatehan, Sriwulan F; Heriyanti, Lesti (UI Scholars Hub, 2021)
Intergroup contact influenced the adaptation capacity of Bugis ethnic in the economic system in the destination site. When they become the highest of social-rank than other ethnicities in livelihood strategies by land-accumulation, it becomes important to analyze the working of power from the ethnic-Social Domination Orientation (SDO) theoretical. The role of ethnic-SDO is studied with assessment determination in a sociocultural context in intergroup ethnic inequality. Moreover, decision making in framing becomes challenged to be assessed at the individual level because it is assumed would influence the individual to enhance the hierarchy in the middle of uncertainty outcomes. This study aims: (1) elucidate the structure of ethnic inequality in livelihood strategies by ethnic-SDO in Bugis ethnic; and (2) recognize the role of framing in decision making as influencing factors of ethnic-SDO. This study approach is qualitative, which involves 25 informants. Data showed that ethnic-SDO in Bugis’s economic activities comprised of power that enhancing-hierarchy evolved ethnic inequality by high between-ethnic group inequality (BGI) and within- ethnic group inequality (WGI) in land-accumulation. It is found that the framing of Bugis people regarding skills and attitudes owned by other ethnicities in the decision-making tends to risk-avoid that enhancing-hierarchy in economic activities at an individual level.